Hyperbola Style In Nizar Qabbani “Asyhadu An Lā Imraata Illa Anti” : Hyperbola Style In Nizar Qabbani “Asyhadu An Lā Imraata Illa Anti” - mawarida, Hanim (LPPM IAI Hasanuddin Pare-Kediri, 2023)
This study discusses the problem of the language style used in the poem